Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„ØªÙƒØ±Ø§Ø± ÙÙŠ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… - Anshori, Muhammad Luthfil (LISANIA: Journal of Arabic Education and Literature, 2017)
This study discusses analytically the phenomenon of repetition (al-takrÃ¢r) contained in the Qur'an. It aims to conceptually describe the phenomenon of repetition in the Qur'an, including: the definitions, types, and functions. The results of this study reveal the disagreements among scholars and academics related to this phenomenon. Some argue that the phenomenon of repetition in the Qur'an is one side of deficiency, or even disgrace that can damage the beauty and majesty of the Qur'an. Yet others argue that it is one common language style used in Arabic literature, which has specific aims and functions. In fact, the repetition gives a deep impact and impression to its readers.